Effects of Combined Ethanol Extract of Anthocleista Vogelii and Alstonia Boonei Stem Barks on Liver Function Indices in Benign Prostatic Hyperplasia Induced Rats (Nigerian Journal of Pharmaceutical Research, 2020)
Objective: This study evaluated the effects of combined ethanol extract of Anthocleista vogelii and Alstonia boonei (CEAA) stem barks on the liver function indices of benign prostatic hyperplasia (BPH)-induced rats.Materials and Methods: Thirty (30) male Wistar rats were randomly grouped into five groups (n = 6). BPH was induced subcutaneously with 5 mg/kg/day of testosterone propionate in olive oil. Groups 1-3 served as normal, BPH control (untreated) and standard drug control respectively, while Groups 4 and 5 were BPH-induced rats and treated with 200 and 400 mg/kg/day of the CEAA respectively after one hour of the BPH induction. After twenty-eight days of treatments, biochemical and histopathological analyses were conducted using standard analytical procedures.Results: The acute toxicity result of CEAA indicated no mortality or adverse reactions. Significant body weight change was only observed in the first week from the group-administered 200 mg/kg/day of CEAA. Liver damage was evident in the BPH control characterized by significant (P